Magma Migration at Shallower Levels and Lava Fountains Sequence as Revealed by Borehole Dilatometers on Etna Volcano - Bonaccorso, Alessandro; Carleo, Luigi; Currenti, Gilda; Sicali, Antonino (Frontiers in Earth Science, 2021)
A main challenge in open conduit volcanoes is to detect and interpret the ultra-small strain (<10–6) associated with minor but critical eruptions such as the lava fountains. Two years after the flank eruption of December 2018, Etna generated a violent and spectacular eruptive sequence of lava fountains. There were 23 episodes from December 13, 2020 to March 31, 2021, 17 of which in the brief period 16 February to 31 March with an intensified occurrence rate. The high-precision borehole dilatometer network recorded significant strain changes in the forerunning phase of December 2020 accompanying the final magma migration at the shallower levels, and also during the single lava fountains and during the entire sequence. The source modeling provided further information on the shallow plumbing system. Moreover, the strain signals also gave useful information both on the explosive efficiency of the lava fountains sequence and the estimate of erupted volume. The high precision borehole dilatometers confirm to be strategic and very useful tool, also to detect and interpret ultra-small strain changes associated with explosive eruptions, such as lava fountains, in open conduit volcanoes.